The development of intensity-duration-frequency curves for Kuantan river basin - Nor Hidayah, Ismail (2016)
Kuantan is one of the flood prone areas that identified in Pahang. The main river basin is Kuantan River. This basin is responsible to drain water from the correspond catchment area to the South China Sea . Due to heavy local rainfall is often occur in the Kuantan area , Kuantan River as main river basin is cannot longer support the volume of the rainfall will causing the flood to the areas surrounding. It is getting worse year by year with heavy rainfall especially at low level area cause of clog drain, design failing, wrong estimation and other natural causes. Besides, the rainfall data in MSMA 2 has not been updated by JPS and it is not reliable to be used as a reference for any hydraulic design. In MSMA 2, only one station which is Sg.Lembing P.C.C.L Mill represent Kuantan district and its intensity parameter will be used for the development project along the Kuantan River Basin. That way may affect the value of intensity should be used for that location area. Thus, the purpose of this study is to develop intensity-duration-frequency (IDF) curve for all 10 station along the Kuantan River Basin based on historical data. Also, to analyse the appropriate frequency analysis in developing IDF curve for Kuantan River Basin and also to compare the rainfall intensity values between MSMA and appropriate frequency analysis for IDF curves. The rainfall data that required for construction of IDF curve is from the Department of Irrigation and Drainage (DID). The data period of 5 minutes to 7200 minutes starting on year 1971 to year 2015. To designing IDF curve, process involved are find the value of mean, standard deviation, frequency factor, rainfall depth and intensity value for 2, 5, 10 ,20, 50 and 100 years return period for both methods Gumbel and Log-Pearson Type III. The range percent of difference intensity between MSMA and new IDF curve is (0.0493%-98.1556%). It is cause by the location of new station either far away or near with the station Sg.Lembing P.C.C.L Mill. Gumbel and Log-Pearson Type III method is used to compare whether it is appropriate to be used for construction of IDF curve for Kuantan River Basin. So, in order to test the accuracy of both methods, Kolmogorov Smirnov (KS) was be used for fitting distribution. Based on the result, mostly Log-Pearson Type III test which is 0/120 test was rejected while Gumbel Distribution showed to fit the graph than Log-Pearson Type III by that accept 120/120 test. So, Gumbel is accepted 100% from all test in Gumbel that can be acceptable compared to LPT III.